Species-dependent protoplast enlargement involves different types of vacuole generation in bacteria - Takahashi, Sawako (Sci Rep, 2020)
Vacuole generation occurs frequently during the enlargement of bacterial protoplasts and spheroplasts. Gram-positive Enterococcus faecalis protoplasts and gram-negative Lelliottia amnigena spheroplasts had large and small vacuoles inside the cytoplasm, respectively. Although no vacuoles were found at the early stage of cell enlargement, all enlarged cells used in the microinjection procedures had vacuoles. The plasma membrane of L. amnigena was more flexible than that of E. faecalis. In addition, E. faecalis protoplasts had unique discoidal structures as well as spherical structures in the cytoplasm. Our findings showed that the number of vacuoles increased as the L. amnigena plasma membrane expanded and that the size of vacuoles increased as the E. faecalis plasma membrane expanded, suggesting that bacterial cell enlargement involved vacuole generation. Thus, biosynthesis of the plasma and vacuolar membranes was synchronous with the bacterial cell enlargement. Differences in the plasma membrane flexibility might influence the different types of vacuole generation.